The Influence of Perceived Usefulness, Perceived Ease Of Use, Perceived Risk And Trust On Interest Using Fintech Shopeepay - Sindy Pratiwi; Ali Sofwan (Jurnal Rekognisi Akuntansi, 2022)
The purpose of the study is to knowing the effect of Perceived Usefulness, Perceived Ease of Use, Perceived Risk and Trust on Interest in using Fintech ShopeePay.The population in this study are students of the Faculty of Economics and Business at the Islamic University of Nahdlatul Ulama Jepara who use ShopeePay. The data used in this study are primary data collected through a questionnaire survey with a total sample of 100 respondents. The sampling technique used is Slovin. The data analysis method used is multiple linear regression analysis with the help of SPSS Versi 20. The results of partial hypothesis testing are known that the Perceived Usefulness variable has no effect on Interest in using ShopeePay Fintech, the Perceived Ease of Use variable has a positive and significant effect on Interest in using ShopeePay Fintech, Perceived Risk variable has no effect on Interest in using ShopeePay Fintech, the Trust variable has a positive and significant effect on Interest in using ShopeePay Fintech